Optimization of plotter printing for sub-terahertz metallic metasurfaces fabrication on ultra-thin substrate. (1st May 2022) - Brulon, Cyprien; Fix, Baptiste; Salmon, Arthur; Bouchon, Patrick
Abstract: Additive manufacturing processes have emerged as a promising way to conceive terahertz and millimetric components. In this work, we discuss a printing process for sub-terahertz metallic metasurfaces fabrication on ultra-thin substrates. We demonstrate the use of a plastic substrate with a micrometric thickness which makes this printing method a promising and low cost alternative to conventional optical lithography for the fabrication of flexible terahertz 2D metasurfaces. After detailing the key parameters and limitations, we applied the optimized process to fabricate samples composed of periodic arrays of split ring resonators on 50 µ m thick fused silica and 3 µ m thick PET substrates. The optical response in transmission of the metasurfaces shows expected resonances in the 100 GHz range and demonstrates the use of microplotter system for rapid prototyping of low-loss terahertz passive components on ultra-thin substrate.